The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/su151914109
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Spatial Distribution of the Genus Cinchona in Peru: Opportunities for Conservation in the Face of Climate Change

Alex J. Vergara,
Dennis Cieza-Tarrillo,
Candy Ocaña
et al.

Abstract: The genus Cinchona belongs to the Rubiaceae family and comprises native Peruvian tree species distributed in tropical areas. It is currently endangered due to human disturbance and overexploitation for medicinal, forestry and food uses. To date, the current and future distribution of Cinchona spp. under the climate change scenario is unknown. Here, we modeled the present and future spatial distribution of the genus Cinchona using bioclimatic, edaphic and topographic variables using the maximum entropy algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 55 publications
(81 reference statements)
1
5
0
Order By: Relevance
“…C. pubescens is found mainly along the slope of the South American Andes [74]. A high probability of encountering these three species can be primarily expected in the central and southern parts of the Amazonas department, a prediction that coincides with Vergara et al [22], who identified this department as having the potential for the occurrence for the entire Cinchona genus in Peru. Another reason for the possible distribution potential of the species in this area is the prevalence of cloud forests (montane forests), which are suitable habitats for the genus [11,75].…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…C. pubescens is found mainly along the slope of the South American Andes [74]. A high probability of encountering these three species can be primarily expected in the central and southern parts of the Amazonas department, a prediction that coincides with Vergara et al [22], who identified this department as having the potential for the occurrence for the entire Cinchona genus in Peru. Another reason for the possible distribution potential of the species in this area is the prevalence of cloud forests (montane forests), which are suitable habitats for the genus [11,75].…”
Section: Discussionsupporting
confidence: 65%
“…This is the first attempt to use the species distribution model (SDM) with the maximum entropy modelling technique to predict and identify areas likely to harbor C. capuli, C. macrocalyx, and C. pubescens in Amazonas [67]. This model has previously been applied at departmental [21], regional [22,68], national, and global levels [20]. In contrast to prior studies on modelling the distribution of the genus [20][21][22]68], this study not only utilized occurrence data from virtual databases, herbarium databases, and floristic inventories, but also included species collected in the field.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations